Biochar: A Guide to Analytical Methods - Singh, Balwant; Camps-Arbestain, Marta; Lehmann, Johannes (CSIRO Publishing, 2017)
Interest in biochar among soil and environment researchers has increased dramatically over the past decade. Biochar initially attracted attention for its potential to improve soil fertility and to uncouple the carbon cycle, by storing carbon from the atmosphere in a form that can remain stable for hundreds to thousands of years. Later it was found that biochar had applications in environmental and water science, mining, microbial ecology and other fields. Beneficial effects of biochar and its environmental applications cannot be fully realised unless the chemical, physical, structural and surface properties of biochar are known. Currently many of the analytical procedures used for biochar analysis are not well defined, which makes it difficult to choose the right biochar for an intended use and to compare the existing data for biochars. Also, in some instances the use of inappropriate procedures has led to erroneous or inaccurate values for biochars in the scientific literature. Biochar: A Guide to Analytical Methods fills this gap and provides procedures and guidelines for routine and advanced characterisation of biochars. Written by experts, each chapter provides background to a technique or procedure, a stepwise guide to analyses, and includes data for biochars made from a range of feedstocks common to all presented methods. Discussion about the unique features, advantages and disadvantages of a particular technique is an explicit focus of this handbook for biochar analyses. Biochar is primarily intended for researchers, postgraduate students and practitioners who require knowledge of biochar properties. It will also serve as an important resource for researchers, industry and regulatory agencies dealing with biochar.